2021
DOI: 10.3390/polym13030435
|View full text |Cite
|
Sign up to set email alerts
|

Model Surfaces for Paper Fibers Prepared from Carboxymethyl Cellulose and Polycations

Abstract: For tailored functionalization of cellulose based papers, the interaction between paper fibers and functional additives must be understood. Planar cellulose surfaces represent a suitable model system for studying the binding of additives. In this work, polyelectrolyte multilayers (PEMs) are prepared by alternating dip-coating of the negatively charged cellulose derivate carboxymethyl cellulose and a polycation, either polydiallyldimethylammonium chloride (PDADMAC) or chitosan (CHI). The parameters varied durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Horvarth et al showed that cationic polyelectrolytes are able to diffuse into the cellulose fiber wall, 52 resembling the mobility of polyelectrolyte chains in polyelectrolyte multilayers. 53,54 Backes et al showed a interdigitation of the dangling ends of a negatively charged P(NIPAM-co-AAc) MG and polymer film from poly(allylamine hydrochloride). 43 The different impact of annealing on the adhesion of CSPs and MGs can therefore be explained by these distinct mechanisms at play.…”
Section: Adhesionmentioning
confidence: 99%
“…Horvarth et al showed that cationic polyelectrolytes are able to diffuse into the cellulose fiber wall, 52 resembling the mobility of polyelectrolyte chains in polyelectrolyte multilayers. 53,54 Backes et al showed a interdigitation of the dangling ends of a negatively charged P(NIPAM-co-AAc) MG and polymer film from poly(allylamine hydrochloride). 43 The different impact of annealing on the adhesion of CSPs and MGs can therefore be explained by these distinct mechanisms at play.…”
Section: Adhesionmentioning
confidence: 99%